Legal Protection Against Child Custody Abandonment Due To Divorce - Meirza Aulia Chairani; Anik Tri Haryani; Krista Yitawati; Bambang Sukarjono; Aldo Ananda Abidin (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2024)
Abstract Introduction to the Problem: The urgency in this research is that many problems arise due to the divorce of parents of children under the age of custody will be given to the mother but mostly after the divorce the father does not provide for his child after the issuance of the divorce. seen from the many cases the government must make a policy for divorced parents the child still gets the nafkah and attention of both parents. Purpose/Study Objectives: The purpose of this research is to see the protection that can be given to the neglect of child custody from divorce. many problems arise in society, one of the parents neglects their children and results in neglected children and does not provide for children for their lives. this is the responsibility of parents in caring for their children. Design/Methodology/Approach: The type of research used in this writing is normative law. The approach used is the statutory approach model and conceptual approach. Findings: In practice what the author encounters is that many parents after the issuance of a divorce the child will become a victim and underage children will especially be given custody of their mother and their father does not provide for the child, sometimes the mother also goes to look for a living to make a living and leaves the child to the mother's parents and here the parents, namely the father, do not exercise their right to provide for the child until they can be independent. Paper Type: Research Article